Approaches to the teaching of introductory literature courses in a Polish English Language Teacher Training College. - Dixon, Andy (Journal of History Culture and Art Research, 2013)
Abstract The purpose of this paper is to outline approaches to a course entitled Introduction to Literature, which is frequently available to second-year undergraduates in Polish teacher training colleges and other institutes of higher education. While preparing students for subsequent courses in British and American literature and helping them towards mature responses to literary texts, the course aims to raise student teachers' awareness of the potential of literature in the learning/teaching situation and to provide them with examples of the integration of curricular areas. In addition, given that literature is an intrinsically interesting source of authentic language, it is intended that instruction should increase students' sensitivity to language and expand their vocabulary, thus promoting the development of the four skills.